Coronary artery cavitation as a trigger for atherosclerotic plaque progression: a numerical and computational fluid dynamic demonstration. (14th October 2021) - Rigatelli, G; Zuin, M; Roncon, L; Nguyen, T
Abstract: Background: Coronary cavitation is supposed to be generated by both concentric and eccentric coronary artery stenosis creating microbubbles which exploded when the fluid pressure was lower than the vapor pressure at a local thermodynamic state. Aims: To assess, using computational fluid dynamic analysis (CFD), the potential role of cavitation in inducing coronary artery endothelial damage and promote atherosclerotic plaque progression. Methods: We retrospectively reviewed the procedural records of consecutive patients evaluated between 1st January 2013 and 1st January 2014 with an isolated hemodynamically significant Left Main (LM) disease. Each bifurcation was reconstructed on the patient-specific geometries derived from the CCTA applying patient-specific hemodynamic features. Vapour has been modelled as discrete vapour bubbles and its trajectory determined using a Lagrangian frame of reference. Cavitation started with micro-cavitation nuclei which subsequently grow into bubbles undergoing different physical processes determined in a stochastic Monte-Carlo approximation. Results: Among the 12 patients analysed [8 males, mean age 68.2±12.8 years old], the mean LM stenosis was 72.3±3.6%. In all subjects, LM stenoses induced cavitation which propagates downstream the vessel. The higher concentration of vapour region was detected before the carina (within 0.8 to 1.3 cm from the stenosis). The mean bubbles radius observed before the carina was 4.2±1.4 μm; their impact with the endothelial surface generated a mean peak pressure of 3.9±0.5 MPa determining a local shockwave (Figure 1). Conclusion: The collapse of micro-bubbles alongside the endothelium generated micro-shockwaves determining repeated dynamic load measurable as an instantaneous pressure-peaks able to induce endothelial injury or dysfunction. Funding Acknowledgement: Type of funding sources: None.